Plan de marketing para el posicionamiento de las tarjetas de crédito del Banco del Austro en la ciudad de Guayaquil. - García Fernández, Emily Susana (2014)
Banco del Austro, with more than three years since it has been created, is a different financial institution, designed to satisfy Ecuadorian needs, people who believe that values such as solidity, efficiency and most of all trustworthiness are vital to found business. This project is a marketing planning proposal with the purpose of improving the positioning of the credit cards from Banco del Austro in Guayaquil and to innovate in its services to achieve a raise in the participation of the market and offer a quality in the customer service. It´s a project based on a field research by collecting data by means of surveys of Banco del Austro of Guayaquil, that own a credit card from the institution; once they were analyzed, and with an interview to the Manager of the Credit Cards of Banco del Austro, it was possible to detect of the data the problem concerning the cards positioning. The result basically showed that the real problem is the need of knowledge of the sale strategies for the positioning of the credit cards; therefore, part of the solution was to design a marketing plan in which the results can be reflected under a fundamental axis, suggested let there be a continuous innovation in the provision of service, the maintenance, positioning of the credit cards, in which the benefits and advantages can shine.